PERBANDINGAN KINERJA PORTOFOLIO BENTUKAN MANAJER INVESTAS! DENGAN MENGGUNAKAN MODEL INDEK TUNGGAL - Umi Murtini; Prayogo Prayogo (Jurnal Riset Akuntansi dan Keuangan, 2007)
The objective of this resurch is to qonine which is the more eficient, portfotio nade by hwestnent Managu or fu ustng Single Index Model. The data used in this resurch is monthly data, from January 2004 untit June 2005. Munnl ftad uses monthly Na Asset Yalue (NAY) data while Single Index Model uses monthly closing price data, stocb that include in the meosurement factars of ILQ-45 from January 2004 until June 2005. Elficient portfolio is decided by comparing risk and return between Mutual Fund's portfolio and Single Index's portfolio. This research eoncludes that Muual Fund's portfolio is more fficient than Single Index's poTtfolio fuause even tlnugh both are earning the samegain but Mutu,al Fund's portfolio has lower risk than Single Index's portfolio.Keywords: portfolio, return, rish Mutual Fund, Single Index Model